2020
DOI: 10.3329/jom.v21i2.50208
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Laboratory Confirmed COVID-19 Cases Admitted in Dhaka Medical College Hospital

Abstract: Background: The objective of the study was to report the epidemiological characteristics of symptomatic laboratory confirmed COVID-19 patients seeking care from Dhaka Medical College Hospital (DMCH). Methods: This observational study was conducted in department of Medicine, DMCH for the period of 2 months following ethical approval. Total 100 RT-PCR confirmed COVID-19 patients were included and interviewed. Informed written consent was ensured before participation. Collected data were entered in a predes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…22.44% of the mild cases was suffering from diabetes; several studies showed the similar result. 17,19 HTN (16.92%) was the 2nd most common comorbidities after DM which was consistent with several studies. 17,23 Only 1.9% patients were suffering from CKD that corresponds with other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…22.44% of the mild cases was suffering from diabetes; several studies showed the similar result. 17,19 HTN (16.92%) was the 2nd most common comorbidities after DM which was consistent with several studies. 17,23 Only 1.9% patients were suffering from CKD that corresponds with other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were reported in other studies in Bangladesh where most of the patients were male (82.67%) and some previous studies showed male were more like 77% and 64%. 6,13,[16][17] It was suggested that ACE2 is the target receptor for COVID-19 that is greatly stated in males than in females which is present. 18,19 Presence of X chromosome and sex hormones may play a role for the less chance of getting infected with the virus in female.…”
Section: Discussionmentioning
confidence: 99%
“…Data supports this concept that several thousand COVID-19 patients died in Europe and the USA, compared to Asian and African countries [17]. In a study in Bangladesh, the researcher found that patients who were dying due to COVID-19 had a significantly higher mean age than the alive group [16]. In the present study, the notable observation was that the highest percentage of patients were in the 60-69 years of age range among both survivors and the non-survivor (35.89%, 33.33%).…”
Section: Discussionmentioning
confidence: 83%
“…In another study published about ICU admitted patients in Bangladesh observed 77.5% of patients were male [5] and death among males was more common than females [14]. In another observation, the severe group contains more than double (29) male patients than female (12) in ICU [16]. We observed a greater percentage of males in survivors (42.42%) and non-survivors (30.3%) than the females (18.18%, 09.09%) in ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation